Pelatihan Pengoperasian Mesin CNC Berbasis Swansoft Simulator Kepada Siswa Teknik Pemesinan di Kota Serang - Haris Abizar; Moh Fawaid; Soffan Nurhaji (Jurnal Pengabdian Pada Masyarakat, 2020)
TRAINING ON OPERATION OF CNC MACHINES BASED ON SWANSOFT SIMULATOR TO MACHINING TECHNIQUE STUDENTS IN SERANG CITY. The CNC machine operation is a potential part that students must master. The limited availability of CNC machines and learning that only prioritizes theory are issues that need to be anticipated. Efforts are being made to provide training in the operation of CNC machines assisted by swansoft simulator software to students. The purpose of this training is to provide stimulation and find out students' responses from CNC machine training assisted by swansoft simulator software. This training activity was attended by 51 students from SMK Agriculture and SMK PGRI 1 in Serang City on machining technique with a simulation model. Retrieval of data used in the questionnaire. This dedication activity produces training that can provide stimulation to master CNC machines by using a swansoft simulator. This is following the response of students who agree with the existence of CNC machine operation training activities assisted by swansoft simulator software so that it helps students to improve their competency in mastering CNC machines.